STUDY OF THE EVALUATION OF 10 KWP ON- GRID SOLAR POWER SYSTEM AT PLTD SIANTAN - Rahmansyah, Agum; Hiendro, Ayong; Khwee, Kho Hie (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
The use of fossil fuels as an energy source remains a primary priority today. However, renewable energy is a potential alternative to support the availability of fossil fuels. Renewable energy is derived from natural sources and has sustainable characteristics, such as solar, wind, and hydro power. Solar Power Plants are one of the electrical energy sources that utilize the sun as their primary source. Indonesia, located on the equator, has abundant solar energy with an average solar radiation intensity of around 4.8 kWh/m^2 per day throughout the country, especially in Pontianak, which is situated on the equator. This research focuses on the evaluation study of an On-Grid Solar Power System located at PLTD Siantan. The objective of this study is to determine the amount of energy generated and conduct economic analysis and feasibility analysis of the On-Grid Solar Power System using three methods: Net Present Value (NPV), Profitability Index (PI), and Payback Period (PP). The data collection and calculations revealed that the average energy produced by the Solar Power System at PLTD Siantan is 29.14 kWp. There are a total of 20 installed solar panels, each with a power of 560W, and one inverter with a capacity of 10 kW. The investment cost for the Solar Power System is IDR. 180,868,506.00. The economic feasibility analysis of the Solar Power System using the three methods resulted in an NPV of IDR. 213,645,234.00, a PI value of 2.18, and a PP value of 14 years